Carbon Emission Disclosure, Intellectual Capital, Capital Structure on Financial Performance and Firm Value - Eny Maryanti; Nafi'atuz Zulfah (Universitas Muhammadiyah Malang, 2025)
Purpose: The purpose of this study was to determine the effect of Carbon Emission Disclosure, Intellectual Capital, Capital Structure on Financial Performance and Firm Value. Methodology/approach: The research method used for this study is quantitative method. The method analysis of this study is multiple linear regression using SPSS 26. Findings: The results show that Carbon Emission Disclosure has a significant effect on Financial Performance and Firm Value, Intellectual Capital has no effect on Financial Performance and Firm Value, Capital Structure has a significant effect on Financial Performance and Firm Value. Practical implications: This study provides implications for companies as material for consideration and knowledge of the factors that can influence Financial Performance and Firm Value. Originality/value: The originality of this study is to combine Carbon Emissions Disclosure, Intellectual Capital, and Capital Structure with Financial Performance and Firm Value. Using five years of data and the latest SPSS analysis, this study uniquely focuses on Indonesian companies in the context of local regulations, thus providing fresh and comprehensive insights